Aging and spirituality: spiritual dimensions of aging theory, research, practice, and policy - Moberg, David O. (Haworth Pastoral Press, 2001)
Ch. 1. The reality and centrality of spirituality -- Ch. 2. The spiritual role of the elder in the Twenty-First Century -- Ch. 3. Spirituality in gerontological theories -- Ch. 4. Research on spirituality -- Ch. 5. Attitudes toward death and dying among persons in the fourth quarter of life -- Ch. 6. Do spirituality and religiosity increase with age? -- Ch. 7. Spiritual care by primary health care providers -- Ch. 8. Spiritual care in hospice settings -- Ch. 9. Integrating spirituality in counseling with older adults -- Ch. 10. Spirituality in social work practice with older persons -- Ch. 11. Secular franciscan spirituality and aging -- Ch. 12. The spiritual life review -- Ch. 13. The role of the chaplain care in spiritual care -- Ch. 14. Toward better care: connecting spirituality to the long-term needs of elders -- Ch. 15. Guidelines for research and evaluation -- Ch. 16. Continuing challenges